Evaluating the validity of a functional electrical stimulation clinical decision making tool: A qualitative study - Abouzakhm, Nathalie; Choy, Samantha; Feld, Rebecca; Taylor, Chris; Carter, Kathryn; Degroot, Spencer; Musselman, Kristin E. (Frontiers in Neurology, 2022)
Introduction Following central nervous system damage, the recovery of motor function is a priority. For some neurological populations, functional electrical stimulation (FES) is recommended in best practice guidelines for neurorehabilitation. However, limited resources exist to guide FES application, despite clinicians reporting that a lack of FES knowledge prevents use in clinical practice. The FES Clinical Decision Making Tool was developed to assist clinicians with FES application and translation into clinical practice. The purpose of this study was to evaluate the content validity of the Tool from the perspectives of Canadian physical and occupational therapists using FES in neurorehabilitation. Methods Thirteen participants (twelve women, one man), aged 40.5 ± 10.3 years, participated in individual semi-structured interviews to explore their clinical decision making experiences when applying FES and to evaluate the content validity (i.e., appropriateness, comprehensibility, and comprehensiveness) of the Tool. Interviews were analyzed using a qualitative conventional content analysis following the DEPICT model. Results Three themes were identified. 1) Clinician context influences FES usage. Participants' experiences with FES use varied and application was influenced by treatment goals. 2) Parameter selection in clinical practice. Participants identified decision-making strategies and the challenges of parameter selection. 3) With modifications, the Tool is a valid resource to inform FES applications. Participants discussed its strengths, limitations, and suggested changes. While the Tool is useful, a more extensive resource (e.g., appendix) for the Tool is warranted. Discussion A revised Tool was created to improve its comprehensiveness and comprehensibility. Thus, the Tool is a valid resource for applying FES in neurorehabilitation.